Comparison of the Effectiveness of Cloud Solutions in Forecasting Using Automated Cloud Machine Learning Solutions - Adam STANKIEWICZ; Adrian P. WOŹNIAK (Communications of International Proceedings, 2022)
Machine Learning is a fast-growing field of data science. Due to its large popularity in both science and business, almost every large company that offer cloud computing services added Machine Learning to its portfolio. In particular, automated machine learning solutions have been added in recent years. Some cloud are still working on such solutions. Others added them very recently (like Amazon in November 2021). The purpose of this paper is to give some insight into automated Machine Learning methods available in the cloud. In particular, the comparison of the efficiency of those cloud solutions.
Keywords: Machine Learning; AutoML; Cloud Computing